Role of Ultrasound Imaging in the Differential Diagnosis of Benign and Malignant Ovarian Cancer - Ismailova, Munojat; Nigmatjonov, Abdurashid; Usmanova, Zilola (International Journal of Psychosocial Rehabilitation, 2020)
The problem of diagnosing and treating tumors and tumor-like formations of the ovaries is complex and extremely urgent not only in connection with the increase in the frequency of the disease but also the severity of the disorders of the reproductive and other body systems caused by them. The identification of a unilocular solid cyst had a positive predictive value for malignancy of 37.1%, while the identification of a multilocular solid cyst had a positive predictive value for malignancy of 43.0% from IOTA framework. Mucinous cystadenocarcinoma was commonly unilateral and involve the presence of irregular thick septa or solid papillary projections that are usually detected within cysts. Therefore, in order to create an easy and simple classification facilitating the differentiation of benign and malignant masses, familiarity with the pattern recognition approach to ultrasound is required.